2010
DOI: 10.1097/coc.0b013e318199fb99
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Vinorelbine and Docetaxel in the Treatment of Advanced Non–Small-Cell Lung Cancer as Frontline and Second-Line Therapy

Abstract: Objectives Combination chemotherapy with third-generation, nonplatinum agents (ie, gemcitabine, vinorelbine, taxanes, or camptothecins) represents a well-tolerated frontline treatment option for metastatic non–small-cell lung cancer and might play a role as salvage therapy as well. The aim of this phase 2 study was to investigate the use of docetaxel and vinorelbine in the frontline and second-line setting in patients with incurable non–small-cell lung cancer. Patients and Methods Seventy-eight patients (42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The articles analyzed the efficacy of platinum, non-platinum or combination therapeutic regimens while also advocating towards specific treatment modalities. Nine studies advocate for combination therapy as an effective treatment regimen for first-line NSCLC [7][8][9][10][11][12][13][14][15], five studies advocate towards non-platinum based therapy as an effective and safer regimen [8,[16][17][18][19], one study concludes that non-platinum based therapy is an effective regimen compared to combination therapy in first-line NSCLC [20], two studies conclude that both non-platinum based regimens and combination therapy show an equal efficacy [21,22], three therapies indicate similar efficacy between platinum-based and non-platinum based regimens [23][24][25], two therapies indicate that the efficacy of non-platinum based therapy is similar to the efficacy of other treatment regimens [26,27], one study states that platinum-based regimens showed a higher efficacy and response rate than non-platinum based regimens [28], 12 studies advocate for non-platinum based regimens as a second line treatment regimen [29][30][31][32][33][34][35][36][37][38][39][40], and two studies advocate towards combination therapy for second-line treatment [41,42]. Most of the articles lean towards the use of combination therapy for first-line treatment and non-platinum based therapy for second-line treatment.…”
Section: A Brief Analysis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles analyzed the efficacy of platinum, non-platinum or combination therapeutic regimens while also advocating towards specific treatment modalities. Nine studies advocate for combination therapy as an effective treatment regimen for first-line NSCLC [7][8][9][10][11][12][13][14][15], five studies advocate towards non-platinum based therapy as an effective and safer regimen [8,[16][17][18][19], one study concludes that non-platinum based therapy is an effective regimen compared to combination therapy in first-line NSCLC [20], two studies conclude that both non-platinum based regimens and combination therapy show an equal efficacy [21,22], three therapies indicate similar efficacy between platinum-based and non-platinum based regimens [23][24][25], two therapies indicate that the efficacy of non-platinum based therapy is similar to the efficacy of other treatment regimens [26,27], one study states that platinum-based regimens showed a higher efficacy and response rate than non-platinum based regimens [28], 12 studies advocate for non-platinum based regimens as a second line treatment regimen [29][30][31][32][33][34][35][36][37][38][39][40], and two studies advocate towards combination therapy for second-line treatment [41,42]. Most of the articles lean towards the use of combination therapy for first-line treatment and non-platinum based therapy for second-line treatment.…”
Section: A Brief Analysis Of Resultsmentioning
confidence: 99%
“…In terms of second-line treatment, 12 articles advocate for the use of non-platinum regimens and they comprise the following study designs: randomized clinical trial [ 29 ], randomized clinical trial [ 30 ], retrospective cohort study [ 31 ], retrospective cohort study [ 32 ], randomized clinical trial [ 33 ], observational study [ 34 ], randomized control trial [ 35 ], review article [ 36 ], randomized clinical trial [ 37 ], randomized clinical trial [ 38 ], observational study [ 39 ], randomized clinical trial [ 40 ] and two studies (randomized clinical trial [ 41 ], randomized control trial [ 42 ]) advocate for the use of combination therapy. On the basis of the articles analyzed, we find an increasing number of articles that advocate towards the use of non-platinum and combination chemotherapeutic modalities.…”
Section: Reviewmentioning
confidence: 99%
“…Although the efficacy and safety of docetaxel in combination with other agents (e.g., erlotinib, vinorelbine, or gemcitabine) has been investigated in the second-line setting, several studies showed no improvement in efficacy and/or increased toxicity with combination therapy over docetaxel alone. [80][81][82][83][84] Furthermore, phase III trials seeking to improve survival by adding targeted agents such as cetuximab 85 or ziv-aflibercept 86 were negative.…”
Section: Second-and Subsequent-line Therapy For Nonsquamous Nsclc Andmentioning
confidence: 99%
“…In a review of seven different recent phase II and III trials of chemotherapy for lung cancer published in major clinical journals, grade three or four adverse events due to dyspnea varied from 3 to 21% [28][29][30][31][32][33][34][35]. In a review of seven different recent phase II and III trials of chemotherapy for lung cancer published in major clinical journals, grade three or four adverse events due to dyspnea varied from 3 to 21% [28][29][30][31][32][33][34][35].…”
Section: Recent Trials Demonstrating Improvement In Dyspnea With Chemmentioning
confidence: 99%